3x(x-5)=4(9+x)

Simple and best practice solution for 3x(x-5)=4(9+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(x-5)=4(9+x) equation:



3x(x-5)=4(9+x)
We move all terms to the left:
3x(x-5)-(4(9+x))=0
We add all the numbers together, and all the variables
3x(x-5)-(4(x+9))=0
We multiply parentheses
3x^2-15x-(4(x+9))=0
We calculate terms in parentheses: -(4(x+9)), so:
4(x+9)
We multiply parentheses
4x+36
Back to the equation:
-(4x+36)
We get rid of parentheses
3x^2-15x-4x-36=0
We add all the numbers together, and all the variables
3x^2-19x-36=0
a = 3; b = -19; c = -36;
Δ = b2-4ac
Δ = -192-4·3·(-36)
Δ = 793
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-19)-\sqrt{793}}{2*3}=\frac{19-\sqrt{793}}{6} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-19)+\sqrt{793}}{2*3}=\frac{19+\sqrt{793}}{6} $

See similar equations:

| H(x)=2x^2-x | | 4×+7y=9,7×+3y=1 | | 4×+7y=9,7×+3y=14×+7y=9,7×+3y=1 | | -3x+3=48 | | -14+8y=-14 | | -6x+33=4x-48 | | 13x2-31x=36 | | -2x+18=28 | | 7^7x=2401 | | 9x+-6-15x+20+8x-13=4 | | 4x-42-126=180 | | 4x-42+126=180 | | 9x+-6-15x+20+8x-13=41 | | 9x-72x3x+18=42 | | (x^2-2x)(2x-2)=0 | | 3x-5/2+4x=-8-3x/2-3 | | 5x^2+3x=25 | | 2(x-1)+3(x-2)=4(x-3) | | y-12+6y+17=180 | | -x-15=-25 | | 5x-2=13+5 | | x^+8x+16-1=3 | | 6+9x=60 | | 8×+24=3x+72 | | 9-0,2x=1 | | 16x+13+18x-1=180 | | 2+7x=6+11x | | 5x(x-6)(4x+9)=0 | | Y=10+12x-3x | | X+15+x+67=180 | | x^2+(x+2)^2=10 | | 2^x+4x+4=10 |

Equations solver categories